Pharmacokinetics and pharmacodynamics of intensive antituberculosis treatment of tuberculous meningitis - Ding, J; Thuy Thuong Thuong, N; Pham, TV; Heemskerk, D; Pouplin, T; Tran, CTH; Nguyen. MTH; Nguyen, PH; Phan, LP; Nguyen, CVV; Thwaites, G; Tarning, J (Wiley, 2020)
The most effective antituberculosis drug treatment regimen for tuberculous meningitis is uncertain. We conducted a randomized controlled trial comparing standard treatment with a regimen intensified by rifampin 15 mg/kg and levofloxacin for the first 60 days. The intensified regimen did not improve survival or any other outcome. We therefore conducted a nested pharmacokinetic/pharmacodynamic study in 237 trial participants to define exposure–response relationships that might explain the trial results and improve future therapy. Rifampin 15 mg/kg increased plasma and cerebrospinal fluid (CSF) exposures compared with 10 mg/kg: day 14 exposure increased from 48.2 hour·mg/L (range 18.2–93.8) to 82.5 hour·mg/L (range 8.7–161.0) in plasma and from 3.5 hour·mg/L (range 1.2–9.6) to 6.0 hour·mg/L (range 0.7–15.1) in CSF. However, there was no relationship between rifampin exposure and survival. In contrast, we found that isoniazid exposure was associated with survival, with low exposure predictive of death, and was linked to a fast metabolizer phenotype. Higher doses of isoniazid should be investigated, especially in fast metabolizers.